2016
DOI: 10.1038/srep37942
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial control through nutritionally regulated global histone H3 lysine-4 demethylation

Abstract: Histone demethylation by Jumonji-family proteins is coupled with the decarboxylation of α-ketoglutarate (αKG) to yield succinate, prompting hypotheses that their activities are responsive to levels of these metabolites in the cell. Consistent with this paradigm we show here that the Saccharomyces cerevisiae Jumonji demethylase Jhd2 opposes the accumulation of H3K4me3 in fermenting cells only when they are nutritionally manipulated to contain an elevated αKG/succinate ratio. We also find that Jhd2 opposes H3K4m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Indeed, a recent study found that Jhd2 physically interacts with CPF (cleavage and polyadenylation factor) and causes defects in mRNA 3′ untranslated region length for some genes ( blair et al 2016 ). More recently, we determined that H3K4 demethylation by Jhd2 occurs not only during sporulation, but also in mitotic cells in response to non-fermentable carbon sources or to nitrogen manipulations that lead to increased levels of alpha-ketoglutarate, an intermediary metabolite essential for demethylase activity of Jhd2 and the entire Jumonji family of demethylases to which JARIDs belong ( liang et al 2007 ; soloveychik et al 2016 ).…”
mentioning
confidence: 99%
“…Indeed, a recent study found that Jhd2 physically interacts with CPF (cleavage and polyadenylation factor) and causes defects in mRNA 3′ untranslated region length for some genes ( blair et al 2016 ). More recently, we determined that H3K4 demethylation by Jhd2 occurs not only during sporulation, but also in mitotic cells in response to non-fermentable carbon sources or to nitrogen manipulations that lead to increased levels of alpha-ketoglutarate, an intermediary metabolite essential for demethylase activity of Jhd2 and the entire Jumonji family of demethylases to which JARIDs belong ( liang et al 2007 ; soloveychik et al 2016 ).…”
mentioning
confidence: 99%
“…(iii) Other organic acids. Cell supernatants were analyzed using acidic reversed-phase LC-MS on an Agilent Technologies 6540 Q-TOF, as previously described (137).…”
Section: Methodsmentioning
confidence: 99%
“…Equal amounts of protein were electrophoresed on SDS-PAGE gels and transferred onto PVDF membranes. Immunoblot analysis was performed as described ( Soloveychik et al 2016 ). Visualization of the proteins was performed by exposing the membrane to light sensitive film.…”
Section: Methodsmentioning
confidence: 99%